Conversion to Sirolimus Therapy in Kidney Transplant Recipients with New Onset Diabetes Mellitus after Transplantation. (20th May 2013) - Veroux, Massimiliano; Tallarita, Tiziano; Corona, Daniela; Sinagra, Nunziata; Giaquinta, Alessia; Zerbo, Domenico; Guerrieri, Carmela; D'Assoro, Antonino; Cimino, Sebastiano; Veroux, Pierfrancesco
Abstract : New-onset diabetes mellitus after transplantation (NODAT) may complicate 2–50% of kidney transplantation, and it is associated with reduced graft and patient survivals. In this retrospective study, we applied a conversion protocol to sirolimus in a cohort of kidney transplant recipients with NODAT. Among 344 kidney transplant recipients, 29 patients developed a NODAT (6.6%) and continued with a reduced dose of calcineurin inhibitors (CNI) (8 patients, Group A) or were converted to sirolimus (SIR) (21 patients, Group B). NODAT resolved in 37.5% and in 80% patients in Group A and Group B, respectively. In Group A, patient and graft survivals were 100% and 75%, respectively, not significantly different from Group B (83.4% and 68%, resp., P = 0.847 ). Graft function improved after conversion to sirolimus therapy: serum creatinine was 1.8 ± 0.7 mg/dL at the time of conversion and 1.6 ± 0.4 mg/dL five years after conversion to sirolimus therapy (P < 0.05 ), while in the group of patients remaining with a reduced dose of CNI, serum creatinine was 1.7 ± 0.6 mg/dL at the time of conversion and 1.65 ± 0.6 mg/dL at five-year followup (P = 0.732 ). This study demonstrated that the conversion from CNI to SIR in patients could improve significantly the metabolic parameters of patients with NODAT, without increasing the risk of acute graft rejection.